An Advanced Pharmacy Practice Experience for Community Pharmacies Based on a Clinical Intervention Targeting Patients With Inflammatory Bowel Disease. (February 2021) - Blackburn, David F.; Fowler, Sharyle; Crawley, Alex; Gerwing, Shauna; Alcorn, Jane; Mansell, Holly; Evans, Charity; Mansell, Kerry; Taylor, Jeff; Jorgenson, Derek; Larocque, Danielle; Rotter, Thomas; et al.
Experiential education is a critical component of any pharmacy undergraduate curriculum. Establishing new, high-quality practice sites can be challenging. We designed a new advanced pharmacy practice experiential rotation suitable for implementation in most community pharmacy settings. The aim of this article is to describe the design of this rotation entitled the Targeted Pharmacy Intervention in Inflammatory Bowel Disease (TPI-IBD) and to determine its impact on student knowledge and confidence using a before-after survey design. The TPI-IBD utilizes a student-delivered intervention as a platform for experiential learning in community pharmacy practice. The TPI was focused on patients with IBD, and implementation was guided by a co-preceptor from the university in collaboration with onsite-preceptors at each pharmacy. The TPI-IBD rotation was delivered from 6 community pharmacies during 5 weeks in 2018. Students conducted standardized monitoring on patients with IBD and met weekly with the university preceptor for case presentations and therapeutic discussions. Electronic charts were maintained by students who were responsible for ensuring detailed documentation on each patient. Knowledge, confidence, and overall satisfaction were assessed by a survey given to students before and after the rotation. Students were highly satisfied with the learning experience and improvements in knowledge and confidence were clearly demonstrated. The TPI strategy was an effective way to expand rotation options in community pharmacy sites with minimal burden on local preceptors.